PELATIHAN IMPLEMENTASI SCIENCE AND TECHNOLOGY INDEX (SINTA) UNTUK DOSEN DALAM UPAYA PENINGKATAN KINERJA PERGURUAN TINGGI - I Made Trisna Semara; Putu Eka Wirawan; I Made Krisna Adi Chandra (Sewagati, 2024)
Performance of science and technology institutions in Indonesia is managed and measured by Sinta. Outreach is needed for lecturers and university verifiers due to its functions. The objectives are 1) to equalize perceptions regarding Sinta's features and facilitation; 2) provide guidance, technical instructions and problem solving in the data verification process for lecturers and institutions at each university; 3) Guide verifiers in universities therefore the quality of the data in Sinta is well maintained. The training methods used are lectures, discussions and group and/or individual tutorials. The results of the activity will be useful for evaluating the performance of lecturers and universities effectively and efficiently in order to increase the number and quality of lecturers' performance as a main purpose of the implementation of the Tri Dharma of Higher Education.